Aplicación del sistema de protección a testigos en el Cantón Otavalo - Erazo Mediavilla, Darwin Renán (2013)
The current plan of Grade’s Project of the APPLICATION OF SYSTEM OF WITNESS PROTECTION, will realize in Otavalo city. This topic gets importance with the reform in Criminal System and Procedural, it ensured for Constitution of year 2008, holding like main tool the system of victim and witness protection. Over that precedent, in 2007 there was a multiple killing at Ranch called “Campo Serio”, it located in San Francisco community, Selva Alegre parish, Otavalo canton, where there was a witness, who was the only survivor. This witness was received to system of victim and witness protection of Imbabura County, because he was afraid today posible attacks against him physical, psychological and moral integrity. His testimony was basic to explain the events and to identic ate to the authors of crime. Therefore, it will study the viability and feasibility of the foundation of a Center of Witness Protection in Otavalo city; this will help to better the application, efficiency and celerity of the criminal process. The current Grade’s Project has a finality of investigate the application of System of Witness Protection through bibliographic roots, legislation, doctrine, compared right, interviews and internet, to diffuse brightly this unknown information in Otavalo canton. In the investigation project the positive impacts waited to have are: social, juristic and politic. The Grade’s Project is structured by five phases, like: the investigation, the develop of Theoretic Frame, of Diagnostic, the Methodology, the analysis of practical expedient and verification of impacts waited. In that Project will use the method bibliographic, historic, analytic -deductive and the comparative. The techniques will use are: the observation, the interview and the research.